Comparative effectiveness of lactulose and sennosides for the prevention of peritoneal dialysis-related peritonitis: an open-label, randomized, active-controlled trial - Kajohnsak Noppakun; Tichanun Narongchai; Romanee Chaiwarith; Uraiwan Wongsawad; Surachet Vongsanim; Chidchanok Ruengorn; Surapon Nochaiwong (Annals of Medicine)
Background To the best of our knowledge, the effectiveness and safety of lactulose in comparison to sennosides, for the prevention of peritoneal dialysis (PD)-related peritonitis, has never been tested in a randomized study.Methods We conducted an open-label, randomized, active-controlled trial in a PD-center in Northern Thailand. Adult patients on PD were enrolled and randomly assigned in a 1:1 ratio into two groups; one group received lactulose 15 mL once daily (n = 50) and the other group received sennosides two tablets daily (n = 50). The primary outcome was time-to-first bacterial peritonitis. The secondary outcomes included a composite of bacterial peritonitis and all-cause mortality. Cox proportional hazards regression was calculated and presented as hazard ratios (HRs) with 95% confidence intervals (CIs).Results One hundred PD patients were recruited (50.0% men; mean age 55.5 ± 13.0 years) in this study. The baseline characteristics of the study participants were similar in both groups. No significant trend towards a higher risk of PD-related peritonitis was observed in the lactulose group (HR, 2.32 [95% CI, 0.92–5.83]; p = .051) compared to the sennosides group. Nevertheless, the secondary outcome was significantly higher in the lactulose group (HR, 2.77 [95% CI, 1.20–6.41]; p = .010). The incidence of adverse events was not substantially different between the two groups; however, diarrhoea was more frequent in the lactulose group (38.0% vs. 18.0%; p = .030) than in the sennosides group.Conclusions Treatment with lactulose is not more effective than sennosides and cannot be routinely recommended for the prevention of peritonitis among the PD population.TRIAL REGISTRATIONThai Clinical Trial Registry (clinicaltrials.in.th); ID: TCTR20171012001KEY MESSAGETo the best of our knowledge, no randomized controlled trial that compares the efficacy and safety profiles of lactulose versus sennosides for the prevention of PD-related peritonitis among the PD population has been conducted.In this open-label, randomized, active-controlled trial, treatment with lactulose is not more effective than sennosides in the prevention of PD-related peritonitis, and it could increase the risk of bacterial PD-related peritonitis.Further studies with a larger sample size by incorporated real-world evidence are needed to confirm our findings and to explore strategies to prevent peritonitis among PD patients.